Use of the index of pulmonary vascular disease for predicting long-term outcome of pulmonary arterial hypertension associated with congenital heart disease - Chida-Nagai, Ayako; Masaki, Naoki; Maeda, Kay; Sasaki, Konosuke; Sato, Hiroki; Muneuchi, Jun; Ochiai, Yoshie; Murayama, Hiroomi; Tahara, Masahiro; Shiono, Atsuko; Shinozuka, Atsushi; Kono, Fumihiko; et al. (Frontiers in Cardiovascular Medicine, 2023)
Aims Limited data exist on risk factors for the long-term outcome of pulmonary arterial hypertension (PAH) associated with congenital heart disease (CHD-PAH). We focused on the index of pulmonary vascular disease (IPVD), an assessment system for pulmonary artery pathology specimens. The IPVD classifies pulmonary vascular lesions into four categories based on severity: (1) no intimal thickening, (2) cellular thickening of the intima, (3) fibrous thickening of the intima, and (4) destruction of the tunica media, with the overall grade expressed as an additive mean of these scores. This study aimed to investigate the relationship between IPVD and the long-term outcome of CHD-PAH. Methods This retrospective study examined lung pathology images of 764 patients with CHD-PAH aged <20 years whose lung specimens were submitted to the Japanese Research Institute of Pulmonary Vasculature for pulmonary pathological review between 2001 and 2020. Clinical information was collected retrospectively by each attending physician. The primary endpoint was cardiovascular death. Results The 5-year, 10-year, 15-year, and 20-year cardiovascular death-free survival rates for all patients were 92.0%, 90.4%, 87.3%, and 86.1%, respectively. The group with an IPVD of ≥2.0 had significantly poorer survival than the group with an IPVD <2.0 (P = .037). The Cox proportional hazards model adjusted for the presence of congenital anomaly syndromes associated with pulmonary hypertension, and age at lung biopsy showed similar results (hazard ratio 4.46; 95% confidence interval: 1.45–13.73; P = .009). Conclusions The IPVD scoring system is useful for predicting the long-term outcome of CHD-PAH. For patients with an IPVD of ≥2.0, treatment strategies, including choosing palliative procedures such as pulmonary artery banding to restrict pulmonary blood flow and postponement of intracardiac repair, should be more carefully considered.